Meta Analysis of Consumer Behavior Changes During The Covid-19 Pandemic Research - Candrawati, Krisnita; Nuvriasari, Audita (Master of Management Diponegoro University, 2021)
The aim of this study is (1) to analyse the development of consumer behaviour research during the Covid-19 pandemic (2) to identify theoretical and empirical contributions from the results of research on consumer behaviour during the Covid-19 pandemic. Co word analysis with VOS Viewer used to answer the first research objective, and quantitative analysis was used to answer the second research objective. The results show that the development of consumer behaviour research during the Covid-19 pandemic is mostly related to the exploration of changes in the types of needs, types of products and priorities of consumer needs during the Covid-19 pandemic. On the other hand, research that needs to be developed is changing online consumer purchasing decisions; Consumer buying behaviour is related to psychological factors, product choice (mainly fresh food ingredients and staple foods), Consistency in purchasing; consistency of changes in consumer habits; awareness and consideration of consumer risk and consumer behaviour during a pandemic. Fundamental theories used in this research include theory of Fear Appeal, Maslow, TAM and TPB. The results showed that there was a model development through the S-O-R computational decision tree ensemble model with Bagging.